2021
DOI: 10.3892/mmr.2021.12557
|View full text |Cite
|
Sign up to set email alerts
|

HIF‑1α in cerebral ischemia (Review)

Abstract: Cerebral ischemic injury may lead to a series of serious brain diseases, death or different degrees of disability. Hypoxia-inducible factor-1α (HIF-1α) is an oxygen-sensitive transcription factor, which mediates the adaptive metabolic response to hypoxia and serves a key role in cerebral ischemia. HIF-1α is the main molecule that responds to hypoxia. HIF-1α serves an important role in the development of cerebral ischemia by participating in numerous processes, including metabolism, proliferation and angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 133 publications
0
16
0
1
Order By: Relevance
“…Under conditions of low oxygen concentrations, the activities of hydroxylases are inhibited. Because of this essential role in oxygen dependent metabolism, HIF-1α plays central roles in a variety of pathophysiological conditions, such as cardiovascular disease, 8 , 9 all forms of ischemic conditions, 10 , 11 osteoarthritis 12 , 13 and tumor biology. 14 , 15 Hence, much effort has been laid on targeting HIF-1α as therapeutic option.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of low oxygen concentrations, the activities of hydroxylases are inhibited. Because of this essential role in oxygen dependent metabolism, HIF-1α plays central roles in a variety of pathophysiological conditions, such as cardiovascular disease, 8 , 9 all forms of ischemic conditions, 10 , 11 osteoarthritis 12 , 13 and tumor biology. 14 , 15 Hence, much effort has been laid on targeting HIF-1α as therapeutic option.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, improving hypoxia ischaemia and neural function was an important way to treat ICS, and HIF-1α, EPO and VEGFA played an important role in the pathogenesis and treatment of cerebral ischaemia (Novikov and Levchenkova 2020 ; Dong et al. 2021 ; Ma et al. 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been proven that HIF-1a regulates up to 70 downstream genes, such as vascular endothelial growth factor, angiogenesis, erythropoietin and so on 21 . Many studies had shown that HIF-1a may play a neuroprotective role in the repair process of brain damage and it might be a potential key mediator of the above described effects 22,23 . Through the reports of these literatures, we can theoretically explain the conclusions of Gao and Zhu et al, such as why the mice learning ability is related to vascular endothelial growth factor, and why intermittent hypoxia can antidepressant-like effects and so on.…”
Section: Discussionmentioning
confidence: 99%